1975
DOI: 10.1530/acta.0.0790295
|View full text |Cite
|
Sign up to set email alerts
|

Combination Contraceptive Effects on Monthly Cycle of Plasma Aldosterone, Renin Activity and Renin Substrate

Abstract: A post-ovulatory peak of fasting supine plasma aldosterone (PA) preceded or accompanied by an increase in plasma renin activity (PRA) was previously reported. These studies have now been extended in 4 additional normal menstruating women and 4 women taking oestrogen\x=req-\ progestogen oral contraceptive pills (OCP), all studied daily for an entire cycle. Distinct luteal phase increases in PRA were seen in the 4 normals, with 2 also demonstrating a rise in PA. Plasma renin substrate (PRS) was usually unvarying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Higher stimulated plasma aldosterone concentrations in younger a n d middleaged women than in men, theoretically, could reflect influence of female sex h o r m o n e s u p o n aldosterone secretion. However, during the menstrual cycle changes in aldosterone secretion are m e d i a t e d by changes in the renin-angiotensin system [15,16]. In our study such a mechanism causing the differences in p l a s m a aldosterone is not conceivable since p l a s m a renin activity statistically not different in the c o m p a rable age-groups between male and female patients occurred.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Higher stimulated plasma aldosterone concentrations in younger a n d middleaged women than in men, theoretically, could reflect influence of female sex h o r m o n e s u p o n aldosterone secretion. However, during the menstrual cycle changes in aldosterone secretion are m e d i a t e d by changes in the renin-angiotensin system [15,16]. In our study such a mechanism causing the differences in p l a s m a aldosterone is not conceivable since p l a s m a renin activity statistically not different in the c o m p a rable age-groups between male and female patients occurred.…”
Section: Discussionmentioning
confidence: 48%
“…A t d o s t e r o n e levels are r e p o r t e d to increase during the menstrual cycle [15,16]. Higher stimulated plasma aldosterone concentrations in younger a n d middleaged women than in men, theoretically, could reflect influence of female sex h o r m o n e s u p o n aldosterone secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogens induce a prompt rise of plasma renin substrate (Helmer & Griffith 1952;Helmer & Judson 1967;Skinner et al 1969;Menard et al 1970) associated with an elevation of plasma renin activity (Crane & Harris 1969;Cain et al 1971 ; Helmer & Griffith 1952) as we indeed observed in the present study. Variable elevation of urinary aldosterone has been observed in women taking oral contraceptives (Crane & Harris 1969;Katz et al 1975;Helmer & Griffith 1952;Menard et al 1970). In the present study, a slight but statistically insignificant elevation of urinary aldosterone was observed after 3 days on ethinyl-oestradiol alone.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs the infusion of angiotensin II (All) has been shown to stimulate the secretion of antidiuretic hormone and to potentiate the liberation of antidiuretic hormone in response to an osmotic load (reviewed by Share 1979). In addition to this action angioten¬ sin exerts a central dipsogenic effect as demon¬ strated by Fitzsimons 1978 CH-1211 Genève 4, Switzerland. added in vitro in the medium bathing isolated rat pituitary glands or intact hypothalamo-neurohypophyseal systems but not isolated rat neural lobes (reviewed by Share 1979 andby Fregly 1978). Oestrogens are known to influence the reninangiotensin-aldosterone system and to modify salt and water balance (Crane & Harris 1969;Cain et al 1971;Menard & Catt 1973;Katz et al 1975). …”
mentioning
confidence: 99%
“…PLASMA renin activity has been reported to be significantly increased in the luteal phase of the menstrual cycle (Brown et al, 1964a;Skinner et al, 1969;Robertson et al, 1971 ;Sundsfjord and Aakvaag, 1973;Katz et al, 1975). Angiotensin I1 levels are also increased at this time (Sundsfjord and Aakvaag, 1970;Robertson et al, 1971).…”
mentioning
confidence: 97%